PENGARUH VARIABEL FUNDAMENTAL TERHADAP HARGA SAHAM DAN LABA PER SAHAM (Studi Kasus Pada Industri Properti Yang Go Public di Bursa Efek Jakarta ) - Wahyu Budi Santoso; Thantawi A.S. - -; Moeljadi - - (Sekolah Pascasarjana Universitas Brawijaya, 2010)
ABSTRACT This research aims at investigating two issues. First, Whether the several fundamental variables simultantly and partially influence toward the stock price and earning per share on property companies that go public at Jakarta Stock Exchange. Second, Which of several fundamental variables have the most dominant influence either toward the stock price or earning per share. Population used in this research include the entire property companies that go public at Jakarta Stock Exchange with criteria that those companies had the data availibility during 4 periods, those are from the year of 1998 until 2001, from that criteria are obtained about 31 companies where the 24 companies were selected as sample with the simple random sampling technically. The method of analysis is Structural Equation Modelling (SEM). Research results indicate that (1) Simultantly, fundamental indicators have the positive influence toward the stock price (Y1) and earning per share (Y2), these are indicated by positive coefficient for the two variables, however the influence to the earning per share are stronger than to the stock price because its coefficient is bigger than another. In addition, partially there are the significant influence for the variables of earning quality (X7), capital expenditure (X3), gross margin (X4), selling and administration expenses (X5) and inventory (X1) because the p-value are smaller than the 5% significant level, while the variables of account recievable (X2), effective tax rate (X6) and labour force (X9) have not the significant influence. (2) And for the variable of earning quality (X7) has the most dominant influence either to the stock price or earning per share because the p-value is the smallest. Â Key Words: Fundamental Analysis, Stock Price, EPS